Between market and myth : the Spanish artist novel in the post-transition, 1992-2014 - Vater, Katie J. (Campos ibericos, 2020)
"In its early transition to democracy following Franco's death in 1975, Spain rapidly embraced neoliberal practices and policies, some of which directly impacted cultural production. In a few short years, the country commercialized its art and literary markets, investing in "cultural tourism" as a tool for economic growth and urban renewal. The artist novel began to proliferate for the first time in a century, but these novels-about artists and art historians-have received little critical attention beyond the descriptive. In Between Market and Myth, Vater studies select authors-Julio Llamazares, Ángeles Caso, Clara Usón, Almudena Grandes, Nieves Herrero, Paloma Díaz-Mas, Lourdes Ortiz, and Enrique Vila-Matas-whose largely realist novels portray a clash between the myth of artistic freedom and artists' willing recruitment or cooptation by market forces or political influence. Today, in an era of rising globalization, the artist novel proves ideal for examining authors' ambivalent notions of creative practice when political patronage and private sector investment complicate belief in artistic autonomy"--